2020
DOI: 10.1186/s10194-020-01140-3
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel headache as a warning symptom of ischemic stroke

Abstract: Background: There are no previous controlled studies of sentinel headache in ischemic stroke. The purpose of the present study was to evaluate the presence of such headache, its characteristics and possible risk factors as compared to a simultaneous control group. Methods: Eligible patients (n = 550) had first-ever acute ischemic stroke with presence of new infarction on magnetic resonance imaging with diffusion-weighted imaging (n = 469) or on computed tomography (n = 81). As a control group we studied in par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…A meta-analysis by Harriott et al found a pooled prevalence of 14%, with an increased risk of headache in the case of cerebral ischemia in the posterior circulation and for the female sex ( 27 ). An analysis of an Israeli stroke register over 2 months including 2,166 patients revealed that 8.4% had suffered from headache and cerebral ischemia, and a large proportion of 28% of patients suffered from TIA and headache ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis by Harriott et al found a pooled prevalence of 14%, with an increased risk of headache in the case of cerebral ischemia in the posterior circulation and for the female sex ( 27 ). An analysis of an Israeli stroke register over 2 months including 2,166 patients revealed that 8.4% had suffered from headache and cerebral ischemia, and a large proportion of 28% of patients suffered from TIA and headache ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Harriott et al found a pooled prevalence of 14%, with an increased risk of headache in the case of cerebral ischemia in the posterior circulation and for the female sex (27). An analysis of an Israeli stroke register over 2 months including 2,166 patients revealed that 8.4% had suffered from headache and cerebral ischemia, and a large proportion of 28% of patients suffered from TIA and headache (28,29). Detailed phenotypic data were documented in only 42% of patients, which is surprisingly low given that this information is essential for classifying the headache according to the current headache classification.…”
Section: Discussionmentioning
confidence: 99%
“…All headaches were diagnosed according to the International Classi cation of Headache Disorders 3rd edition (ICHD-3) [ 5]. We de ned sentinel headache as a new type of headache or a previous kind of headache with altered characteristics (severe intensity, increased frequency, absence of effect of drugs) which arose within seven days before stroke [3].…”
Section: De Nitions and Diagnostic Criteriamentioning
confidence: 99%
“…The ICHD-3 does not include diagnostic criteria for sentinel headache before an ischemic stroke. Our previous study [3] characterized sentinel headache before ischemic stroke in 550 patients with rst-ever ischemic stroke, we propose explicit diagnostic criteria for sentinel headache. Totally 94 patients had headaches within the last week before a stroke and 12 in the control group.…”
Section: Type Of Headachementioning
confidence: 99%
See 1 more Smart Citation